THE CONCEPT OF "TAX GAP" AT THE MICRO LEVEL AND THE SPECIFIC CHARACTERISTICS OF ITS CALCULATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Article 266 of the current Tax Code defines the conditions for crediting the paid value added tax. As a basis for calculating the value added tax according to this article, the fact that the tax is shown in the invoices or that the tax is paid to the budget in the case of goods being brought (imported) is taken as the main criteria. In practice, due to the fact that the value added tax is generated through electronic invoices and the fact that the payment of value added tax in the customs authorities is shown electronically on personal cards, it has become easier to establish control over the correct crediting of the tax. Nevertheless, there are problems in the implementation of control over whether the tax is actually paid to the budget by the counterparties when purchases are made from the domestic market, and whether it is correctly shown in the reports.